2022
DOI: 10.7759/cureus.25401
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glucosamine and Chondroitin Sulfate in the Prevention of Colorectal Cancer: A Systematic Review

Abstract: Currently, colorectal cancer is the third most common cancer in the world. Recently, glucosamine and chondroitin have gained popularity for their beneficial effects on cancer. They have already been recognized for their therapeutic role in osteoarthritis. This systematic review aims to analyze the relationship between the combined consumption of glucosamine and chondroitin and the prevention of colorectal cancer. Three databases: PubMed, Google Scholar, and Science Direct, were searched to collect relevant art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(65 reference statements)
0
2
1
Order By: Relevance
“…For colorectal cancer, previous findings have been inconsistent. Four of seven studies in a latest systematic review reported significantly reduced risk of colorectal cancer incidence associated with glucosamine use, but the other three studies did not find statistical significance as in our analysis ( 17 ). In addition, our study suggested possible associations for the increased risk of melanoma and lower risk of kidney and thyroid cancers, although not statistically significant, which should be further investigated.…”
Section: Discussioncontrasting
confidence: 76%
“…For colorectal cancer, previous findings have been inconsistent. Four of seven studies in a latest systematic review reported significantly reduced risk of colorectal cancer incidence associated with glucosamine use, but the other three studies did not find statistical significance as in our analysis ( 17 ). In addition, our study suggested possible associations for the increased risk of melanoma and lower risk of kidney and thyroid cancers, although not statistically significant, which should be further investigated.…”
Section: Discussioncontrasting
confidence: 76%
“…However, weight gain was reported in those who consumed the supplement more frequently or simultaneously used non-steroidal anti-inflammatory drugs. However, this study did not confirm which drug was responsible for the weight gain [ 96 ]. Therefore, it is suggested that consuming CS more than the recommended dose should be avoided.…”
Section: Prospective Pharmacological Applicationmentioning
confidence: 99%
“…The relevant studies were screened, distilled, and collected by two independent researchers, anonymously through the Rayyan Software (Rayyan Systems Inc., Cambridge, Massachusetts) [ 16 ]. The intervention and outcome were carefully and closely monitored and extracted.…”
Section: Reviewmentioning
confidence: 99%